Analysis of Correspondence Reviews Texts and Stars Ratings (MCIT: Proceedings of International scientific and practical conference, 2020)
The article analyses the connection between the clients’ reviews of the texts and their published  ratings. To realize the task the language R and the packages such as jsonlite, tm, SnowballC, wordcloud, RColorBrewer, ggplot2 and others have been chosen. We used the data of the service Yelp, opened for academic goals and analysis [6]. For the analysis we used sentiment analysis. Sentiment analysis is the computational treatment of opinions, sentiments and subjectivity of text.
Keywords: Sentiment analysis, Emotion detection, Yelp, corpus, textual review, positive words, negative words, clouds of the words